Advanced Technologies, Systems, and Applications II Proceedings of the International Symposium on Innovative and Interdisciplinary Applications of Advanced Technologies (IAT) - Hadžikadić, Mirsad; Avdaković, Samir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents innovative and interdisciplinary applications of advanced technologies. It includes the scientific outcomes of the 9th DAYS OF BHAAAS (Bosnian-Herzegovinian American Academy of Arts and Sciences) held in Banja Vrućica, Teslić, Bosnia and Herzegovina on May 25-28, 2017. This unique book offers a comprehensive, multidisciplinary and interdisciplinary overview of the latest developments in a broad section of technologies and methodologies, viewed through the prism of applications in computing, networking, information technology, robotics, complex systems, communications, energy, mechanical engineering, economics and medicine, to name just a few.
Keywords: Computational intelligence; Dynamics; Nonlinear theories; Biomedical engineering; Mechanical engineering; Electric power production; Computational Intelligence; Applied Dynamical Systems; Biomedical Engineering and Bioengineering; Mechanical Engineering; Electrical Power Engineering; Mechanical Power Engineering